Computational Evidence of NAGNAG Alternative Splicing in Human Large Intergenic Noncoding RNA. (5th June 2014) - Sun, Xiaoyong; Lin, Simon M.; Yan, Xiaoyan
Abstract : NAGNAG alternative splicing plays an essential role in biological processes and represents a highly adaptable system for posttranslational regulation of gene function. NAGNAG alternative splicing impacts a myriad of biological processes. Previous studies of NAGNAG largely focused on messenger RNA. To the best of our knowledge, this is the first study testing the hypothesis that NAGNAG alternative splicing is also operative in large intergenic noncoding RNA (lincRNA). The RNA-seq data sets from recent deep sequencing studies were queried to test our hypothesis. NAGNAG alternative splicing of human lincRNA was identified while querying two independent RNA-seq data sets. Within these datasets, 31 NAGNAG alternative splicing sites were identified in lincRNA. Notably, most exons of lincRNA containing NAGNAG acceptors were longer than those from protein-coding genes. Furthermore, presence of CAG coding appeared to participate in the splice site selection. Finally, expression of the isoforms of NAGNAG lincRNA exhibited tissue specificity. Together, this study improves our understanding of the NAGNAG alternative splicing in lincRNA.